Partisipasi Orang Tua Dalam Mengembangkan Kecerdasan Intrapersonal Anak: Studi Kasus pada Anak Usia 5–6 Tahun di RW 09 Desa Sukakarsa Kecamatan Sukarame - Ulpiyati, Alin; Elan, Elan; Mulyadi, Sima (Edusia: Jurnal Ilmiah Pendidikan Asia, 2021)
Parental participation is very basic in the development of a child's character, one of which is intelligence. Intrapersonal intelligence is very important for children, if someone has a high level of intelligence, he will be able to control his emotions so that the actions taken are based on the correct knowledge. Therefore, in developing this intrapersonal intelligence, a stimulus from parents is needed. The purpose behind this research is to describe the role of parents in developing intrapersonal intelligence of children aged 5-6 years. The researcher uses a case study approach approach, the type of instrumental case study approach. The selection of research subjects was carried out by purposive sampling, which consisted of two families. This information collection method is carried out using interviews, observation, and documentation. This study uses data analysis techniques created by Miles and Huberman. The results showed that parents play a role in providing support, parents play a role in providing guidance, parents play a role in uniting children's activities, parents play a role in providing understanding for children, parents teach children in emotions, parents play a role in habituation to children.